A new genus of terraranas (Anura: Brachycephaloidea) from northern South America, with a systematic review of Tachiramantis. Issue 1 (31st December 2022) - Arroyo, Sandy; Targino, Mariane; Rueda-Solano, Luis Alberto; Daza, Juan M.; Grant, Taran
Abstract : Since the systematics of Terrarana frogs was overhauled in 2008, five new genera have been named, including Tachiramantis from the Venezuelan Coastal Range and adjacent parts of the Cordillera Oriental of Colombia and the Sierra de Perijá along the Venezuela–Colombia border. The discovery of Tachiramantis raises questions about the relationships of several species of Pristimantis in the nearby Sierra Nevada de Santa Marta previously hypothesized to be closely related to species now referred to Tachiramantis . To test the monophyly of Tachiramantis and the relationships among its species, we generated DNA sequences for 42 individuals, and, given the variable placement of Tachiramantis in previous studies, analysed them with DNA sequences from GenBank representing 25 genera of terraranas. In total, the final matrix included DNA sequences from 414 terminals, which we analysed using tree-alignment under the parsimony optimality criterion. To identify morphological synapomorphies and diagnostic characters, we also examined cranial osteology and axial skeleton morphology. Our analyses corroborated both the placement of Tachiramantis far from Pristimantis in Craugastoridae and the monophyly of Tachiramantis . We also found that six species currently referred to Pristimantis, all endemic to the Sierra Nevada de Santa Marta, comprise the sister clade of Tachiramantis. This highly endemic clade is both well-supported by molecular data and diagnosed from Tachiramantis by seven morphological synapomorphies, leading us to recognize it as a new genus. http://zoobank.org/urn:lsid:zoobank.org:act:0036039F-F400-4CD4-A6AD-D3DD2B34BA4E